Evaluation of the relationships between physico-chemical parameters and the abundance of Vibrio spp. in blue crabs (Callinectes sapidus) and seawater from the Maryland Coastal Bays - Smalls, Jasmine; Jacobs, John; Townsend, Howard; Chigbu, Paulinus; Parveen, Salina (Frontiers in Microbiology, 2024)
Fluctuations in water quality characteristics influence the productivity of blue crabs (Callinectes sapidus), and the risk of human exposure to pathogenic Vibrio species. Thus, this study assessed the prevalence of total and pathogenic markers of Vibrio parahaemolyticus and Vibrio vulnificus in blue crabs and seawater from the Maryland Coastal Bays (MCBs) and the correlation between Vibrio levels and physicochemical factors. Three to five crabs and one liter of seawater were collected monthly for three years (May 2018 to December 2020) from six sites within the MCBs. Hemolymph and crab tissue were extracted and pooled for each site. Extracted hemolymph, crab tissue, and seawater were analyzed for V. parahaemolyticus and V. vulnificus using the Most Probable Number (MPN) and real-time PCR methods. A one-way Analysis of Variance (ANOVA), correlations, and linear models were used to analyze the data. Akaike Information Criterion (AICc) was evaluated to determine the model that provides the best fit to the data relating to Vibrio concentrations and environmental factors. Results suggested that environmental factors could influence the growth of Vibrio spp. Both V. parahaemolyticus and V. vulnificus were more prevalent during the warmer months than colder months. Vibrio was more prevalent in crab samples compared to seawater. Vibrio vulnificus concentrations in seawater and hemolymph were positively correlated with temperature (p = 0.0143 seawater) and pH (p = 0.006 hemolymph). A negative correlation was observed between the concentration of V. vulnificus in whole crab (tissue) and dissolved oxygen level (p = 0 .0256). The concentration of V. parahaemolyticus in seawater was positively correlated with temperature (p = 0.009) and negatively correlated with dissolved oxygen (p = 0.012). These results provide current information on the spatial and temporal distributions of Vibrio spp. in the MCBs that are useful for implementing more efficient processing and handling procedures of seafood products.